Global trends of textile waste research from 2005 to 2020 using bibliometric analysis - Kasavan S.; Yusoff S.; Guan N.C.; Zaman N.S.K.; Fakri M.F.R. (Springer Science and Business Media Deutschland GmbH, 2023)
adsorption; cluster analysis; concentration (composition); detection method; spatiotemporal analysis; wastewater; wastewater treatment; China; bibliometrics; China; human; technology; textile; wastewater; Bibliometrics; China; Humans; Technology; Textiles; Waste Water